A Zr-containing NdFeB magnet and its preparation method and application
By adding Zr elements to the neodymium iron boron magnets, ZrC particles are generated, which reduces the C content in the Nd-rich phase, solves the problems of traditional neodymium iron boron magnets demagnetization and poor corrosion resistance at high temperatures, and improves the coercive force and magnetic performance stability of the magnets.
Patent Information
- Application Number
- CN202411689207.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Traditional neodymium iron boron magnets are prone to demagnetization at high temperatures and have poor corrosion resistance, which limits their application in harsh environments such as new energy vehicles.
By adding element Zr to the magnet, reacting with C dissolved in the Nd-rich phase to generate strong carbide ZrC particles, which significantly reduces the C content in the Nd-rich phase, thereby increasing the coercive force of the magnet.
It improves the coercive force of neodymium iron boron magnets, enhances its magnetic performance stability at high temperatures, and is suitable for harsh environments such as new energy vehicles.
Smart Images

Figure CN119170369B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of NdFeB magnets, and in particular to a Zr-containing NdFeB magnet and a preparation method and application thereof. Background Art
[0002] Sintered NdFeB magnets are widely used in motors, information technology, medical equipment and other fields due to their excellent magnetic properties. However, traditional NdFeB magnets are prone to demagnetization at high temperatures and have poor corrosion resistance, which limits their application in certain harsh environments. High-energy motors used in new energy vehicles, in particular, have high requirements on magnet performance, requiring magnets to have high remanence and high coercive force.
[0003] The microstructure of sintered NdFeB magnets includes main phase grains and grain boundary phases. There are two main types of grain boundary phases: one is a triangular grain boundary phase distributed between multiple main phase grains, and the other is a thin layer of grain boundary phase mainly distributed between two main phase grains. At present, NdFeB magnets are mainly prepared by powder metallurgy. During the preparation process, a certain amount of lubricant and antioxidant needs to be added to the powder. These additives can significantly reduce the oxygen content of the powder and improve the orientation of NdFeB particles during orientation pressing. However, the added lubricant and antioxidant are generally organic matter. During the sintering process, the carbon in these organic matter cannot be completely volatilized, and some carbon will remain in the magnet. The residual carbon will subsequently dissolve in the Nd-rich phase, reducing the coercive force of the material and causing the magnetic properties of the magnet to decrease. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a Zr-containing NdFeB magnet and a preparation method thereof. During the preparation process, the element Zr is added to the magnet to react with C dissolved in the Nd-rich phase to form strong carbide ZrC particles, which significantly reduces the C content in the Nd-rich phase and thereby improves the coercive force of the magnet.
[0005] The present invention provides a Zr-containing NdFeB magnet, comprising a main phase grain and a grain boundary phase, wherein the main phase grain is composed of R2Fe 14 B; ZrC particles are distributed in the grain boundary phase; the grain boundary phase includes a two-grain thin layer grain boundary phase and a triangular grain boundary phase, wherein the two-grain thin layer grain boundary phase is located between any two main phase grains, and the triangular grain boundary phase is located between any three or more main phase grains.
[0006] Furthermore, within any range where ZrC particles can be observed, the total area of the triangular grain boundary phase is recorded as S, and the area of the triangular grain boundary phase containing ZrC particles is recorded as S1, wherein 0.3≤S1 / S≤0.8.
[0007] Preferably, the S1 / S is 0.33, 0.45, 0.51, 0.56, 0.72, 0.77, etc.
[0008] Furthermore, within any range where ZrC particles can be observed, the total number of ZrC particles is recorded as N, the number of ZrC particles between two thin-layer grain boundary phases is recorded as N1, and the number of ZrC particles in the triangular grain boundary phase is recorded as N2, where 0≤N1 / N≤0.1 and 0.9≤N2 / N≤1.
[0009] Preferably, N1 / N is 0.01, 0.03, 0.06, 0.09, etc.; N2 / N is 0.92, 0.94, 0.97, 0.99, etc.
[0010] Furthermore, the ZrC particle size is between 10nm and 500nm.
[0011] Preferably, the ZrC particle size is 12nm, 23nm, 47nm, 106nm, 173nm, 245nm, 387nm, 466nm, etc.
[0012] Furthermore, the NdFeB magnet comprises the following elements by mass percentage: 28.5-31.5% R, 0.05-0.5% Zr, 1.0-2.5% M, 0.85-0.97% B, and the balance is Fe; wherein R contains Nd and also contains at least one of Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc; and M contains at least one of Cr, Co, Ni, Ga, Cu, Al, Ti, Nb, Mo, Sn, Hf, and W.
[0013] Another aspect of the present invention is to provide a method for preparing a Zr-containing NdFeB magnet, comprising the following process:
[0014] (1) preparing raw materials according to the composition of the magnet and preparing R-Fe-B-Zr-M alloy ribbons by a rapid solidification ribbon method;
[0015] (2) The alloy strip obtained in step (1) is subjected to hydrogen explosion and air flow milling with additives to obtain alloy powder.
[0016] (3) adding a lubricant and an antioxidant to the alloy powder obtained in step (2), and then mixing the alloy powder in a mixer to obtain a powder to be pressed;
[0017] (4) pressing the powder obtained in step (3) under magnetic field orientation to obtain a compact;
[0018] (5) vacuum sintering the green compact obtained in step (4) to obtain a sintered green compact;
[0019] (6) The sintered green body obtained in step (5) is subjected to multi-stage aging treatment to obtain a final magnet.
[0020] Furthermore, the average particle size of the alloy powder obtained in step (2) is 2.3-5.5 μm, preferably 2.5 μm, 3.6 μm, 3.9 μm, 4.5 μm, 5.2 μm, etc.
[0021] Furthermore, during the mixing in step (3), a lubricant and an antioxidant are added to the magnetic powder and mixed for 0.5-3 hours, and the amount of the lubricant and antioxidant added is 0.1-0.5wt%.
[0022] Furthermore, the sintering process of step (5) is as follows: heating the green body to 250-350°C and keeping it warm for 0.5-3.5h; then heating it to 900-1000°C and keeping it warm for 5-10h; then cooling it to 750-850°C and keeping it warm for 2-4h; and finally heating it to 1000-1080°C and sintering it for 1-6h.
[0023] Furthermore, in the sintering process of step (5), the heating rate is 5°C / min-10°C / min, and the cooling rate is 10°C / min-20°C / min.
[0024] Furthermore, the multi-stage aging treatment in step (6) includes a primary aging treatment and a secondary aging treatment: the primary aging treatment is to keep the temperature at 850-950°C for 3-5 hours; the secondary aging treatment is to keep the temperature at 450-600°C for 0.5-5 hours.
[0025] As a preferred embodiment of the present invention, the step (6) may also optionally include subjecting the sintered NdFeB magnet obtained in the step (5) to diffusion treatment.
[0026] Preferably, the diffusion treatment is a grain boundary diffusion treatment, the diffusion temperature is 800-970° C., and the diffusion time is ≥5 h.
[0027] Preferably, the diffusion treatment may also be at least one of the treatment methods known in the art, such as coating, sputtering, and dipping.
[0028] Preferably, the diffusion source of the diffusion treatment is selected from at least one of the elements Dy, Tb, Ho, Nd and Pr.
[0029] As a preferred embodiment of the present invention, before the diffusion treatment, a pretreatment known in the art may be performed, including but not limited to processing the sintered NdFeB magnet into a required size, and then degreasing, pickling, etc.
[0030] On the other hand, the present invention also provides the use of the Zr-containing NdFeB magnet in a motor.
[0031] The advantages of the present invention are:
[0032] The invention provides a Zr-containing sintered NdFeB magnet. Zr, a strong carbide-forming element, is added into the magnet. During the sintering process, Zr reacts with C dissolved in a Nd-rich phase to generate ZrC particles in situ. A large number of ZrC particles exist in a triangular grain boundary phase. The ZrC particles have a melting point of 3540°C and are very stable. After being generated, they will not dissolve into the Nd-rich phase, thereby reducing the content of C dissolved in the Nd-rich phase and improving the coercive force of the magnet. Meanwhile, a small amount of ZrC particles are generated in a two-grain thin-layer grain boundary phase. The ZrC particles in the two-grain thin-layer grain boundary phase can hinder the growth of main phase grains, thereby further improving the coercive force of the magnet. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 TEM image of ZrC particles;
[0034] Figure 2 for Figure 1 Diffraction pattern of ZrC particles in the
[0035] Figure 3 Schematic diagram of the triangular grain boundary containing ZrC particles, the triangular grain boundary without ZrC particles, and the ZrC particles in the two-grain thin layer grain boundary of the Zr-containing NdFeB magnet prepared in Example 1 of the present invention.
[0036] Figure 4 This is a SEM image of the Zr-containing NdFeB magnet prepared in Example 1 of the present invention, and the circled particles in the image are ZrC particles. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the invention to clearly and completely describe the technical solutions in the embodiments of the invention. Obviously, the described embodiments are only part of the embodiments of the invention, not all of them. Based on the embodiments in the invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the invention.
[0038] It should be noted that the various installation methods and technical terms mentioned in the invention are technical terms that have long been clearly known in the relevant technical field, so no further explanation is given. In addition, the same reference numerals are used for the same components, but this does not affect and should not constitute an accurate understanding of the technical solution by those skilled in the art.
[0039] Example 1 In this example, raw materials were prepared according to the formula in Table 1 to prepare a Zr-containing NdFeB magnet. The specific preparation process steps are as follows:
[0040] (1) The alloy flakes are prepared by the rapid solidification thin sheet method, and the alloy powder is prepared by the hydrogenation and dehydrogenation method;
[0041] (2) jet milling the obtained alloy powder to obtain alloy powder with a particle size of 3.6 μm;
[0042] (3) adding 0.3 wt% of a lubricant and an antioxidant to the alloy powder obtained by jet milling in step (2), and then mixing the powder in a mixer for 3 h to obtain a powder to be pressed;
[0043] (4) Pressing the mixed powder under an oriented magnetic field with a magnetic field strength of 2 T to obtain a green body;
[0044] (5) The green body is placed in a vacuum furnace for sintering. The sintering process is as follows: heating to 300°C at a rate of 8°C / min and keeping the temperature for 2.5 hours; then heating to 950°C at a rate of 8°C / min and keeping the temperature for 7 hours; then cooling to 800°C at a rate of 15°C / min and keeping the temperature for 3 hours; finally heating to 1050°C at a rate of 8°C / min and sintering for 5 hours to obtain a sintered magnet.
[0045] (6) The sintered magnet is subjected to multi-stage aging treatment: the first-stage aging temperature is 920°C and the insulation time is 5 h, the second-stage aging temperature is 510°C and the insulation time is 4 h, and the second-stage aging is completed by rapid cooling to obtain the final Zr-containing NdFeB magnet.
[0046] Example 2 The magnet composition of this example is the same as that of Example 1, except that the content of Zr element is different, as shown in Table 1.
[0047] The preparation process of this embodiment is the same as that of embodiment 1, except that the parameters of the sintering process are different. The sintering process of this embodiment is as follows: heating to 300°C at a rate of 8°C / min and keeping the temperature for 2.5 hours; then heating to 950°C at a rate of 8°C / min and keeping the temperature for 7 hours; then cooling to 820°C at a rate of 15°C / min and keeping the temperature for 4 hours; finally heating to 1050°C at a rate of 8°C / min and sintering for 5 hours. Finally, a sintered magnet is obtained.
[0048] Example 3 The magnet composition and preparation process of this example are the same as those of Example 1, except that the element content is different, as shown in Table 1.
[0049] Example 4 The magnet composition and preparation process of this example are the same as those of Example 1, except that the element content is different, as shown in Table 1.
[0050] Comparative Example 1 The magnet composition and preparation process of this comparative example are the same as those of Example 1, except that the Zr element is not added in this comparative example, as shown in Table 1 for details.
[0051] Comparative Example 2 The magnet composition of this comparative example is the same as that of Example 1, except that the preparation process is different, as shown in Table 2 for details.
[0052] Comparative Example 3 The magnet composition of this comparative example is the same as that of Example 1, except that the preparation process is different, as shown in Table 2 for details.
[0053] Comparative Example 4 The magnet composition of this embodiment is the same as that of Example 1, except that the preparation process is different, as shown in Table 2 for details.
[0054] Table 1 Composition and content of the magnets of the embodiments and comparative examples
[0055]
[0056] Table 2 Differences in sintering process between Example 1 and Comparative Examples 2-4
[0057]
[0058] For Comparative Example 2, compared with Example 1, there is no third stage of heat preservation. After being kept at 950° C. for 7 hours, the temperature is directly increased to 1050° C. at a rate of 8° C. / min and sintered for 5 hours.
[0059] For Comparative Example 3, compared with Example 1, the third stage is lowered to a lower holding temperature, and the temperature is lowered to 700°C at a cooling rate of 15°C / min and kept at that temperature for 3 hours, and then the temperature is increased to 1050°C at a rate of 8°C / min and sintered for 5 hours.
[0060] For Comparative Example 4, compared with Example 1, there is no second and third stage heat preservation, and after being kept at 300° C. for 2.5 hours, the temperature is increased to 1050° C. at a rate of 8° C. / min and sintered for 5 hours.
[0061] Test Case
[0062] The embodiments and comparative examples were tested for performance, and the results were as follows:
[0063] Analysis of morphological results:
[0064] The scanning electron microscope was used to observe and analyze Example 1. Figure 4As shown, it can be seen that there are many small square ZrC particles in the magnet structure, with particle sizes ranging from 10nm to 200nm. In addition, there are very few particles in the two-grain thin-layer grain boundary, accounting for only 4% of the total number of particles. Most ZrC particles are distributed in the triangular grain boundary, and the area ratio of the triangular grain boundary containing ZrC particles to the total triangular grain boundary is 56% (the two-grain thin-layer grain boundary refers to a very thin layer of grain boundary phase located between any two main phase grains in the magnet microstructure, and the two grains refer to two main phase grains; the triangular grain boundary refers to the triangular grain boundary phase in the three-fork grain boundary region between any three or more main phase grains in the magnet microstructure).
[0065] Figure 1 is a TEM photograph of Example 1, Figure 1 It can be seen that there are two small ZrC particles, and the size of the large particle is about 100nm. The diffraction analysis of the particle shows the diffraction spots as follows: Figure 2 As shown. Figure 2 The diffraction spots were analyzed and the results showed that the crystal structure of the particles was exactly the same as that of ZrC particles, which was a face-centered cubic structure.
[0066] Magnetic properties analysis:
[0067] The magnetic properties of the embodiment and comparative example 1 were tested, and the results are shown in Table 3. It can be seen from Table 3 that the results of embodiment 1 and comparative example 1 show that the remanence of the two is basically the same, but the coercive force of embodiment 1 is significantly higher than that of comparative example 1. The main reason for the different magnetic property results is that Zr is added in embodiment 1, and Zr reacts with C in the Nd-rich phase during the sintering process to generate ZrC, which reduces the C content in the Nd-rich phase, and a small amount of ZrC is generated in the two-grain thin layer grain boundary, which hinders the growth of grains during the sintering process, and finally makes embodiment 1 show more excellent magnetic properties.
[0068] The coercivity of Example 2 is higher than that of Example 1, but its remanence is slightly lower. The main reason is that more Zr added leads to more and larger ZrC particles, the volume fraction of the main phase decreases, and its remanence decreases slightly. More ZrC particles further hinder the growth of grains, and further reduce the C content in the Nd-rich phase, ultimately making its coercivity slightly higher than that of Example 1.
[0069] Since Comparative Examples 2-4 were not carried out according to the sintering and heat preservation process described in the claims, their remanence and coercive force were lower than those of Example 1.
[0070] Through research, it is found that the solubility of Zr and C elements in the Nd-rich phase gradually increases with the increase of temperature. After the temperature is lowered after being kept at a certain temperature, due to the decrease in the solubility of Zr and C in the Nd-rich phase, they precipitate from the Nd-rich phase and react to form ZrC particles. Comparative Example 2 did not perform the third stage of heat preservation to 750-850°C, resulting in fewer ZrC particles generated, uneven distribution, and fewer triangular grain boundaries containing ZrC particles, so its coercivity is lower than that of Example 1. The third stage heat preservation temperature of Comparative Example 3 is lower, down to 700°C. Although the ZrC particles generated are slightly more than those in Example 1, they are still lower than those in Example 1. The triangular grain boundaries containing ZrC particles are still less, resulting in its coercivity being lower than that of Example 1. Comparative Example 4 did not perform the second and third stage heat preservation, and the generated ZrC was the least, the triangular grain boundaries containing ZrC particles were also the least, and its coercivity was the lowest.
[0071] Table 3 Comparison of magnet properties between the embodiment and the comparative example
[0072]
[0073] For those skilled in the art, the invention is not limited to the details of the above exemplary embodiments, and can be implemented in other specific forms without departing from the spirit or basic characteristics of the invention; therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the invention is defined by the appended claims rather than the above description, so it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any reference numerals in the claims should not be regarded as limiting the claims involved.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any minor modifications, equivalent substitutions and improvements made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the technical solution of the present invention.
Claims
1. A Zr-containing NdFeB magnet comprising main phase grains and grain boundary phases, characterized in that: ZrC particles are distributed in the grain boundary phase; the composition of the main phase grains is R2Fe 14 B; the grain boundary phase includes a two-grain thin layer grain boundary phase and a triangular grain boundary phase, wherein the two-grain thin layer grain boundary phase is located between any two main phase grains, and the triangular grain boundary phase is located between any three or more main phase grains; In any range where ZrC particles can be observed, the total area of the triangular grain boundary phase is recorded as S, and the area of the triangular grain boundary phase containing ZrC particles is recorded as S1, where 0.3≤S1 / S≤0.8; The preparation method of the Zr-containing NdFeB magnet comprises the following process: rapid solidification → hydrogen explosion → air flow milling → mixing → pressing → sintering → multi-stage aging treatment, wherein the sintering process is: heating the green body to 250-350°C and keeping the temperature for 0.5-3.5h; then heating the green body to 900-1000°C and keeping the temperature for 5-10h; then cooling the green body to 750-850°C and keeping the temperature for 2-4h; and finally heating the green body to 1000-1080°C and sintering for 1-6h.
2. A Zr-containing NdFeB magnet according to claim 1, characterized in that: In any range where ZrC particles can be observed, the total number of ZrC particles is recorded as N, the number of ZrC particles between two thin-layer grain boundary phases is recorded as N1, and the number of ZrC particles in the triangular grain boundary phase is recorded as N2, where 0≤N1 / N≤0.1 and 0.9≤N2 / N≤1.
3. A Zr-containing NdFeB magnet according to claim 1, characterized in that: The ZrC particle size is between 10nm and 500nm.
4. A Zr-containing NdFeB magnet according to claim 1, characterized in that: The NdFeB magnet comprises the following components by mass percentage: 28.5-31.5% R, 0.05-0.5% Zr, 1.0-2.5% M, 0.85-0.97% B, and the balance is Fe; wherein R contains Nd and also contains at least one of Y, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Sc; and M contains at least one of Cr, Co, Ni, Ga, Cu, Al, Ti, Nb, Mo, Sn, Hf, and W.
5. A Zr-containing NdFeB magnet according to claim 1, characterized in that: The heating rate in the sintering process is 5°C / min-10°C / min, and the cooling rate is 10°C / min-20°C / min.
6. The method for preparing a Zr-containing NdFeB magnet according to claim 1, characterized in that: During the mixing process, 0.1-0.5 wt % of lubricant and antioxidant are added to the magnetic powder, and the mixing is performed for 0.5-3 hours.
7. The method for preparing a Zr-containing NdFeB magnet according to claim 1, characterized in that: The multi-stage aging treatment includes a primary aging treatment and a secondary aging treatment: the primary aging treatment is to keep the temperature at 850-950° C. for 3-5 hours; the secondary aging treatment is to keep the temperature at 450-600° C. for 0.5-5 hours.
8. Use of the Zr-containing NdFeB magnet according to claim 1 in a motor.
Citation Information
Patent Citations
R-t-b based permanent magnet
CN110299234A